Leukocyte Telomere Length and All-Cause Mortality: A Between-Within Twin Study With Time-Dependent Effects Using Generalized Survival Models. Issue 10 (29th June 2018) - Zhan, Yiqiang; Liu, Xing-Rong; Reynolds, Chandra A; Pedersen, Nancy L; Hägg, Sara; Clements, Mark S
Abstract: Although previous studies examining leukocyte telomere length (LTL) and all-cause mortality controlled for several confounders, the observed association could be biased due to unmeasured confounders, including familial factors. We aimed to examine the association of LTL with all-cause mortality in a Swedish twin sample while adjusting for familial factors and allowing for time-dependent effects. A total of 366 participants (174 twin pairs and 18 individuals) were recruited from the Swedish Twin Registry. LTL was assessed using the Southern blot method. All-cause mortality data were obtained through linkage with the Swedish Population Registry, updated through November 15, 2017. To control for familial factors within twin pairs, we applied a between-within shared frailty model based on generalized survival models. Overall, 115 (31.4%) participants were men and 251 (68.6%) were women. The average age of the study participants when blood was drawn was 79.1 years, and follow-up duration ranged from 10 days to 25.7 years (mean = 10.2 years). During the follow-up period, 341 (93.2%) participants died. Shorter LTL was associated with higher mortality rates when controlling for familial factors in the between-within shared frailty model. We found significant time-dependent effects of LTL on all-cause mortality, where the mortality rate ratios were attenuated with increasing age.